2009
DOI: 10.1090/s0273-0979-09-01277-4
|View full text |Cite
|
Sign up to set email alerts
|

Representation theory of symmetric groups and related Hecke algebras

Abstract: Abstract. We survey some fundamental trends in representation theory of symmetric groups and related objects which became apparent in the last fifteen years. The emphasis is on connections with Lie theory via categorification. We present results on branching rules and crystal graphs, decomposition numbers and canonical bases, graded representation theory, connections with cyclotomic and affine Hecke algebras, Khovanov-Lauda-Rouquier algebras, category O, W -algebras, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 197 publications
(299 reference statements)
1
55
0
Order By: Relevance
“…It has been suggested that all graded decomposition numbers of F p S d might have zero coefficients in negative powers of q, which is equivalent to saying that graded adjustment matrices (defined by equation (5)) have integer entries: cf. remarks in [2, Subsection 5.6] and [7,Subsection 10.3]. Using the aforementioned results, we find examples showing that this is not the case when p = 2 (Corollary 6).…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…It has been suggested that all graded decomposition numbers of F p S d might have zero coefficients in negative powers of q, which is equivalent to saying that graded adjustment matrices (defined by equation (5)) have integer entries: cf. remarks in [2, Subsection 5.6] and [7,Subsection 10.3]. Using the aforementioned results, we find examples showing that this is not the case when p = 2 (Corollary 6).…”
Section: Introductionmentioning
confidence: 55%
“…subject to a lengthy list of relations given in [1] (see also, for example, [7]). In particular, the relations ensure that the elements e(i), i ∈ I d , are pairwise orthogonal idempotents summing to 1.…”
Section: Graded Cyclotomic Hecke Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…The q-analogue of decomposition numbers d λ,µ (q) is defined by considering the graded multiplicity of D µ inside S λ and we refer to [Kle10] for details regarding its definitions and properties. Lascoux, Leclerc and Thibon conjectured in [LLT96] that when F = C, the d λ,µ (q)'s are the same coefficients in the expansion of the lower global crystal basis {G(µ) | µ ∈ P is b-regular} explained as follows.…”
Section: Iwahori-hecke Algebras and Conjecturesmentioning
confidence: 99%
“…By Lemma 4.4, each indecomposable projective summand of W k (γ|δ) is isomorphic to some Q(α|β). By the 'wedge' shape of the decomposition matrix of S n with columns labelled by p-restricted partitions (see for instance [20,Theorem 5.2]) and Brauer reciprocity, the ordinary character of P α contains the irreducible character χ α exactly once. Hence the ordinary character of Q(α|β) contains the character…”
Section: 2mentioning
confidence: 99%